Hidden in the Same Mystery: Thomas Merton and Loretto - Hart, Patrick (Cistercian studies quarterly, 2011)
The article reviews the book "Hidden in the Same Mystery: Thomas Merton and Loretto," by Bonnie Thurston, Mary Swain, and Paul Quenon.